Haematophagus Mites in Poultry Farms of Iran - S Rahbari; S Nabian; H Ronaghi (Tehran University of Medical Sciences, 2009)
Background: Blood sucking mites are important avian ectoparasites which being found on bird species worldwide. Their presence are problematic for the producers either through potential direct effects on weight gain, egg production, sperm production in roosters or as nuisance pests on worker handle hens and eggs. The aim of this study was pointing out of the status of haematophagus mites. Methods: Eight caged layer and four breeder flocks were visited, monitoring for the presence of chicken mites performed by removing and examining debris from poultry house, infested nesting material collected into zip lock plastic bags and at least 20 birds were also randomly selected to examine the presence of chicken mites. Mites obtained from each population were mounted in Hoyer,s medium on microscope slides and identified. All eight caged layer and four breeder flocks were inspected, which were infested with chicken blood feeding mites. Results: Massive infestations of Dermanyssus gallinae were common with huge numbers of parasites on birds, cages and the conveyor belts for egg. Only one farm from Mazandaran Province was infested to Ornithonyssus bursa. Conclusion: Dermanyssus gallinae was the most prevalent blood feeder mite in the breeder and caged layer flocks in Iran, while O. bursa was reported as a first record, which found only in a breeder flock in Mazanderan Province. It seems that its presence is limited into the area which affected by both warm and humid environmental conditions.